Characterisation of Activity Based Costing on Remanufacturing Crankshaft - Mohd Yazid, Abu; K. R., Jamaludin; Muhammad Aizzat, Zakaria (Universiti Malaysia Pahang, 2017)
Traditional cost accounting applied by most remanufacturing industries assumes that manufacturing overheads are driven by the volume of production. However, this would not give a good measure of the actual manufacturing cost per unit because the overheads should actually be apportioned over the number of activities that are required to perform. Eventually, the cost of remanufactured crankshaft becomes obviously incorrect while the profitability becomes vague. The aim of this work is to estimate the cost of remanufactured crankshaft using activity based costing. The overhead costs are apportioned to activity drivers in accordance with the way resources are consumed and then, the overhead costs are apportioned from each activity driver to each cost object in proportion to the amount of the cost driver consumed by the product. The proposed method is validated by an industrial practitioner and expected to be able to serve as a useful approach because it produces a cost with accurate allocation of overhead, provides cost information on the cost drivers and produces accurate manufacturing cost and profitability information. This work is also supported by the Ministry of International Trade and Industry of Malaysia by proposing accurate allocation of overhead to strengthen the national remanufacturing policies for the development of remanufacturing industries as these industries need to sustain their end of life products.